RANCANG BANGUN SISTEM MONITORING KUALITAS UDARA DAN REDUKSI PARTIKULAT BERBASIS INTERNET OF THINGS - Hariawan, Bramantia Rayhan; Maulana, Eka; Setyawati, Onny (Jurnal Mahasiswa TEUB, 2025)
This study discusses the design and implementationof an Internet of Things (IoT)-based air quality monitoringsystem capable of detecting PM2.5 particles, carbon dioxide(???), temperature, and humidity. The system utilizesGP2Y1010AU0F, MQ-135, and DHT22 sensors integrated withan ESP32 microcontroller. Environmental data is transmittedin real-time to the Thinger.io platform and displayed through aThinger.io based application connected to Firebase. The systemis also equipped with automated features such as a mist maker,LED indicators, and a buzzer that activate when pollutionlevels exceed the established thresholds based on Indonesia'sMinistry of Health Regulation No. 7 of 2019. Test results showthat the system effectively detects and responds to poor airconditions and that the sensors demonstrate high accuracycompared to reference instruments. This system has thepotential to be further developed as a mitigation tool for airpollution impacts on public health in indoor and semi-enclosedenvironments.Keywords - Internet of Things, air quality, PM2.5sensor, carbon dioxide, Thinger.io, ESP32